International and National Perspectives on the Corporate Social Responsibility: A Harbinger of Quality Change - Ahmad, Towseef (SUSURGALUR, 2016)
ABSTRACT: CSR (Corporate Social Responsibility) has been around for a long time and seems to have a timeless concern for reputation, ethics, and values of a corporation. However, the modern and the scientific era of CSR began with the publication of the first definitive work entitled âSocial Responsibilities of the Businessmanâ by Howard R. Bowen (1953); and later the publication of âStrategic Management: A Stakeholder Approachâ by R. Edward Freeman (1984). This article tries to elaborate, by using the literature and theoritical review, the international and national perspectives on CSR. The CSR concept has been subjected to a lot of managerial and professional opinions, discussions, and research. In spite of the seemingly endless discussion and research about its contours, it has seen a lot of growth and development in both academic circles and practitioner communities all over the world. It is an exemplar of commitment to improve the well being of a community through social and environmental stability vetted with the concept of sustainability, benevolent business practices, and responsible stakeholder investment in different ways, which assumesÂ a greatÂ significance and is assayed within the framework. KEY WORD: Corporate Social Responsibility; Stakeholder; Corporations; Principles; Quality.Â IKHTISAR: âPerspektif Internasional dan Nasional tentang Tanggungjawab Sosial Perusahaan: Sebuah Perubahan Kualitas a la Harbingerâ. CSR (Tanggungjawab Sosial Perusahaan) telah hadir dalam waktu lama dan memiliki kepedulian abadi dalam hal reputasi, etika, dan nilai-nilai dari suatu perusahaan. Namun, era modern dan ilmiah tentang CSR dimulai dengan publikasi karya definitif pertama yang berjudul âTanggung Jawab Sosial Pengusahaâ oleh Howard R. Bowen (1953); dan kemudian publikasi âManajemen Strategis: Sebuah Pendekatan Pemangku Kepentinganâ oleh R. Edward Freeman (1984). Artikel ini mencoba untuk menguraikan, dengan menggunakan kajian literatur dan teoritis, perspektif internasional dan nasional tentang CSR. Konsep CSR ini telah mengalami banyak pendapat, diskusi, dan kajian dari para manajer dan golongan profesional. Terlepas dari diskusi dan kajian yang tak berujung tentang kontur CSR, ianya telah mengalami banyak pertumbuhan dan perkembangan di kalangan akademisi dan praktisi di seluruh dunia. Ini adalah sebuah contoh komitmen untuk meningkatkan kesejahteraan masyarakat melalui stabilitas sosial dan lingkungan tentang konsep keberlanjutan, praktek bisnis yang baik, dan investasi pemangku kepentingan yang bertanggung jawab dengan cara berbeda, yang mengasumsikan sebuah kerangka dengan makna besar dan teruji.KATA KUNCI: Tanggungjawab Sosial Perusahaan; Pemangku Kepentingan; Korporasi; Prinsip; Kualitas.About the Author: Towseef Ahmad is an Assistant Professor (Contractual) at the University of Kashmir, Srinagar, India. For academic interests, the author is able to be contacted via phone number at: 8803924342 or via e-mail at: towseefahmad7@gmail.comHow to cite this article? Ahmad, Towseef. (2016). âInternational and National Perspectives on the Corporate Social Responsibility: A Harbinger of Quality Changeâ in SUSURGALUR: Jurnal Kajian Sejarah & Pendidikan Sejarah, Vol.4(1), March, pp.1-12. Bandung, Indonesia: Minda Masagi Press and UBD Bandar Seri Begawan, Brunei Darussalam, ISSN 2302-5808. Chronicle of the article: Accepted (March 17, 2015); Revised (October 9, 2015); and Published (March 24, 2016).